Developing Digital Teaching Media for Indonesian Sign Language (BISINDO) - R, Nabillah; Setiaji, Hari (Teknodika, 2023)
This research raises questions about learning Indonesian Sign Language (BISINDO), which still needs more resources to help people learn it outside of a single sign class. Since it makes people who learn it quickly forget the material, there needs to be more material to be studied repeatedly. Hence, a website-based sign language learning media application was developed with the Join Application Design (JAD) research method to overcome these problems. With the JAD method, stakeholders were observed and interviewed, and a team was assembled to design the application. This research focused on the application's feasibility by testing it through usability testing. The indicators in ISO 9421-11 were used to test how well the developed application worked regarding convenience, efficiency, and satisfaction. The test results revealed an average value of 60–70% with a good category, so this Indonesian Sign Language digital teaching aid can be utilized. However, it can still be developed to be better.